The Use of Public Expenditure for Distributive Purpose - Robin W. Boadway; Maurice Marchand (Queen's University, Department of Economics, 1990)
Governments typically used expenditures extensively as redistributive devices. Examples include the public provision of health, education, welfare, and public pensions. The purpose of this paper is to investigate the normative rationale for such policies. In particular, we study the role of government expenditures as purely redistributive devices given that the government also has available to it an optimal non-linear income tax. We do so in the context of specific types of quasi-private expenditures meant to represent education and pensions, both of which could have been provided privately. We assume that public provision to an individual cannot be related to individual characteristics or income , so it is uniform across individuals. We derive a set of sufficient conditions for the use of public expenditures in the presence of optimal taxes. The conditions are similar to those which would make subsidies to private provision welfare-improving. Subsidization and public provision appear to be substitute policies. Which one would be preferable depends upon the global characteristics of the economy.
Keywords: 330